Students' Multiple Representations and Attitude toward Learning University Physics - Kuo, Yen-ruey; Treagust, David; Zadnik, Marjan; Siddiqu, Salim (National Taiwan Normal University, 2011)
This case study was conducted with first year students who were enrolled in non-major Physics units in a university in Australia. Two questionnaires on the topic of Thermal Physics and Optics, respectively, were designed for assessing students' conceptual understanding of the way in which multiple representations (description using words, diagrams, formulas and coordinate graphs) were used to explain the concepts. Students also responded to a Physics Expectation Survey, a Physics Experience Survey and a Physics Motivation Survey to gain an understanding of their attitude toward studying Physics. The Physics Expectation Survey and the Physics Experience Survey, which are pre and post-test respectively, showed there was no significant difference between students' expectations and actual experience. The two surveys also showed students' expectations and experience were in upper-intermediate level. As for the Physics Motivation Survey, it revealed that on average students had a positive attitude towards learning Physics. Besides, the questionnaires that assessed students' conceptual understanding of multiple representations in Physics showed that there was a significant increase in the number of students' different representations after changing the format of the questions. However, a large number of students were unable to solve the questions effectively on the questionnaires no matter the format of the questions had been changed or not.